Long-Term Effects of Moderate Concussive Brain Injury During Adolescence on Synaptic and Tonic GABA Currents in Dentate Granule Cells and Semilunar Granule Cells - Gupta, Akshay; Dovek, Laura; Proddutur, Archana; Elgammal, Fatima S.; Santhakumar, Vijayalakshmi (Frontiers in Neuroscience, 2022)
Progressive physiological changes in the hippocampal dentate gyrus circuits following traumatic brain injury (TBI) contribute to temporal evolution of neurological sequelae. Although early posttraumatic changes in dentate synaptic and extrasynaptic GABA currents have been reported, and whether they evolve over time and remain distinct between the two projection neuron classes, granule cells and semilunar granule cells, have not been evaluated. We examined long-term changes in tonic GABA currents and spontaneous inhibitory postsynaptic currents (sIPSCs) and in dentate projection neurons 3 months after moderate concussive fluid percussion injury (FPI) in adolescent rats. Granule cell tonic GABA current amplitude remained elevated up to 1 month after FPI, but decreased to levels comparable with age-matched controls by 3 months postinjury. Granule cell sIPSC frequency, which we previously reported to be increased 1 week after FPI, remained higher than in age-matched controls at 1 month and was significantly reduced 3 months after FPI. In semilunar granule cells, tonic GABA current amplitude and sIPSC frequency were not different from controls 3 months after FPI, which contrast with decreases observed 1 week after injury. The switch in granule cell inhibitory inputs from early increase to subsequent decrease could contribute to the delayed emergence of cognitive deficits and seizure susceptibility after brain injury.